Instrument for resonance accuracy and misconception analysis (IRAMA): Development to identify sound wave conceptions with rasch - Aminudin, Adam Hadiana; Syamsiah, Endah Nur; Taufani, Muhammad Rizka; Prasetia, Yuda; Samsudin, Achmad; Zahran, Muhammad (Journal of Environment and Sustainability Education, 2026)
The Instrument for Resonance Accuracy and Misconception Analysis (IRAMA) was developed to identify college students’ sound wave resonance conceptions with Rasch. The Identify, Design, Development, Evaluation (IDDE) was used with 30 participants (9 females and 21 males) from one of the universities in Bandung, and four experts (2 in physics and 2 in education) served as IRAMA validators. Rasch analysis used Minifac 4.4.0 (MF-RM) with the rater reliability of 0.75, Infit-MnSq values of 0.77–1.38, and Outfit-MnSq values are outside the ideal limits on item 5 (3.72) (the rest is ideal).  With Jamovi 2.7.2, we confirmed the presence of bias in one of the raters for item 5. The Ministep 5.10.1, based on conceptual categories, Full Understanding (FU), Partial Plus (PP), Partial Minus (PM), Don't Understand (DU), Misconception (MC), and Not Defined (ND). Meanwhile, identification for confidence is based on Full Confidence (FC), Partial Confidence (PC), Not Confidence (NC), and Not Defined (ND). The Cronbach Alpha reliability for conception (0.84), with the highest being in the PM category (27%), and the lowest is in the DU and ND categories (10%). For confidence, the Cronbach Alpha reliability (0.91), with the highest category is in FC (77%), and the lowest is in the ND category (6%). IRAMA is also free from bias towards gender for conception and confident answers (PROB>5% and meet the threshold DIF Contras). Thus, the IRAMA can be an instrument to identify resonance conceptions and, in the future, will be an tool in resonance Augmented Reality (AR) application.